Ultrastructure of endothelial cells of blood capillaries of the femoral muscle after a simulated gunshot fragmentation wound. - Lurin, I. A.; Mikhaylusov, R. N.; Negoduyko, V. V.; Nevzorov, V. P. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. The study at the subcellular level of organelles of endothelial cells of skeletal muscle capillaries allowed us to detail the duration and features of regeneration of newly formed capillaries of muscle tissue after gunshot wounds. Objective. Detection of features of reconstructions of submicroscopic architectonics of endothelial cells of skeletal muscle capillaries at different times after gunshot wound. Methods. Experimental modeling of gunshot wounds of soft tissues was performed on 20 breeding rabbits, which inflicted gunshot wounds on the hip muscle area of the Fort pistol. Pieces of scar tissue from the wound canal were removed for electron microscopic examination with magnification of 20000-60000 folds at 30 and 60 days after injury. Results. In the formed scar tissue 30 days after the gunshot wound, the nuclear membrane of the endothelial cells had a loose appearance and formed numerous small invaginations. Lumps of condensed chromatin were located in the nuclei, which concentrated along the nuclear membrane. The cytoplasm of endothelial cells contained a small number of small mitochondria with single crystals. The membranes of the rough endoplasmic reticulum are moderately loosened, lose a well-contoured structure, and the tanks are flattened. After 60 days, the cytoplasm of the vast majority of endothelial cells contained a large number of polys and ribosomes, sometimes located in clusters. The nuclei of the endothelial cells had an irregular elongated shape. The nuclear membrane formed multiple deep and small invaginations. Lumps of condensed chromatin, localized on the inner membrane of the nucleus and had a high degree of osmiophilia. The central region of the nucleus matrix had a low electron density and was filled with diffusely scattered granules of decondensed chromatin and ribosomes. The perinuclear space was enlarged and had the appearance of electron-transparent vacuoles. Conclusion. Changes in the intracellular organelles of endothelial cells of the blood capillaries of the muscles found at 30 days after the gunshot wound are associated with hypoxic intracellular processes occurring in the mitochondria. Data obtained at 60 days indicates a chronic course of dystrophic process.